2015
DOI: 10.1016/j.acvd.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Are cardiovascular trial results systematically different between North America and Europe? A study based on intra-meta-analysis comparisons

Abstract: There is some evidence to support the theory that, relative to controls, interventions are more favoured in cardiovascular trials conducted in Europe than in North America, when treatment efficacy is measured in terms of a non-fatal endpoint. However, the overall support for systematic differences in cardiovascular trial results between Europe and North America is weak, which may be surprising given the amount of data collected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 78 publications
(62 reference statements)
1
0
0
Order By: Relevance
“…However a few δ 13 C values slightly lower than -22‰ found in one aurochs from southern Sweden and two moose from Denmark reflect some early stages of forest succession. This is consistent with vegetational reconstructions that indicate relatively open landscape in Denmark and northern Germany during this period [ 70 ], [ 85 ], [ 86 ], [ 87 ]. Geological, pollen-botanical and zoological investigations have shown that northern Germany and the south of Denmark was a park tundra (steppe-tundra and forest-steppe with birch and pine), while the north-west of Denmark was covered by open tundra dominated by dwarf shrubs and willows [ 88 ].…”
Section: Discussionsupporting
confidence: 90%
“…However a few δ 13 C values slightly lower than -22‰ found in one aurochs from southern Sweden and two moose from Denmark reflect some early stages of forest succession. This is consistent with vegetational reconstructions that indicate relatively open landscape in Denmark and northern Germany during this period [ 70 ], [ 85 ], [ 86 ], [ 87 ]. Geological, pollen-botanical and zoological investigations have shown that northern Germany and the south of Denmark was a park tundra (steppe-tundra and forest-steppe with birch and pine), while the north-west of Denmark was covered by open tundra dominated by dwarf shrubs and willows [ 88 ].…”
Section: Discussionsupporting
confidence: 90%